Stress assessment in patients with clinically diagnosed sleep bruxism - Miletić, Ana; Lazić, Zoran; Todorović, Ana; Djordjević, Igor; Popović, Danica; Lazić, Vojkan (Vojnosanitetski pregled, 2020)
Background/Aim. Many studies investigated association between stress, anxiety or personality traits and sleep bruxism (SB), but results are still contradictory. We aimed to investigate whether there is a relation between clinically diagnosed sleep bruxism and salivary cortisol levels as one of the major stress biomarkers and to examine psychological factors and personality traits specific to sleep bruxism. Methods. A total of 23 sleep bruxism patients and 42 healthy non-sleep bruxism adults participated in this study. Diagnose of sleep-bruxism was assessed by self-report and clinical examination and also confirmed by bed-partner. Morning saliva was collected from all participants for analyses of the cortisol level. Sleep bruxism patients underwent a psychodiagnostic personality interpretation using the Minnesota Multiphasic Personality Inventory – MMPI-202 test. Results. Statistically significant difference between levels of morning salivary cortisol in the group of SB patients and the control group was recorded (t = 2.943, p < 0.01). Analysis of the personality profiles indicated that the sleep bruxism patients avoid contact with unpleasant feelings, especially depression, suppress the aggression and censor the expression of anger and rage. Conclusion. This study showed that patients with sleep bruxism have higher levels of salivary cortisol. Personality traits such as depression, hypomania and suppressed aggression were found to be common characteristics in patients with sleep bruxism. Present findings might support the hypothesis that sleep bruxism and psychological states such as stress may be related, but the cross-sectional nature of this study does not allow us to draw conclusions about the causal relationship between stress, personality traits and sleep bruxism.